ESTABLISHING STRATEGIC DEVELOPMENT IN EXTENDING THE SАNОАT KОRXОNАLАRI INNОVАTSIОN FAМАRАDОR - Asimova Feruza Abdusattorovna; Zagidullina Kamila Rafailovna; Sayfutdinova Nigina Furkatovna (Bright Mind Publishing, 2025)
The importance of organization of strategic management in improving the efficiency of innovation activities of industrial enterprises is studied. Innovation is a necessary factor for ensuring the competitiveness of the industrial enterprises, increasing economic growth and sustainable development. Thanks to the effective organization of strategic management, enterprises can increase their innovation potential, develop new products and technologies, and improve production processes.
Keywords: Industrial enterprises, innovative activities, strategic management, efficiency, competitiveness, economic growth, technology, products, management strategies, organizational change, leadership, innovative potential, global market, strategic decisions.